Fine Needle Aspiration Cytology of Cutaneous Metastatic Lesions: A Clinico-Cytopathological Perspective in A Tertiary Hospital - Mohapatra, Manisha; Satyanarayana, Sridhara; Venkatachalam, Turlapati SatyaPrakash (Annals of Pathology and Laboratory Medicine, 2018)
Background: Cutaneous metastasis refers to growth of cancer cells in skin from an internal malignancy which indicates an adverse prognosis for the cancer patient. Fine needle aspiration cytology (FNAC) plays a major role in early diagnosis of such lesions. The study was undertaken in a tertiary hospital in south India with an objective to analyze the cases diagnosed as having metastatic lesions by FNAC with special reference to cutaneous metastasis. Methods: The study consisted of retrospective analysis of all the cases diagnosed in our hospital as having metastatic lesions in various locations based on FNAC over a period of 7 years of which cases with cutaneous metastatic lesions were studied in detail. FNAC was done following routine protocols, stained smears were examined and opined by experienced pathologists. The result was analyzed. Result: A total number of 579 cases were diagnosed to be having metastatic lesions in various sites based on FNAC findings out of which 61(10.5%; Female-44, Male-17) cases had cutaneous metastasis. Majority, 35/61 (57.2%) cases was in 5th to 6th decade. Fifty eight ( 95.0% ) of cases presented with metastasis in single site whereas 3(5.0%) cases had lesions in multiple sites. The commonest primary malignancy in females and males was carcinoma breast and carcinoma colon or lung respectively. Conclusion: This study depicts the clinical and cytopathological findings of patients with cutaneous metastatic lesions with known or unknown primaries and highlights the utility of FNAC in diagnosing such lesions which helps the clinicians to take prompt decision for further therapeutic management.